2014
DOI: 10.1111/jgh.12390
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection for duodenal carcinoid tumors: A multicenter, retrospective study

Abstract: Endoscopic resection appears to be a safe and effective treatment for duodenal carcinoid tumors measuring ≤ 10 mm in diameter and confined to the submucosal layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
124
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 21 publications
14
124
3
3
Order By: Relevance
“…Corresponding results were also reported in the previous studies of D-NET [5,19,22]. In addition, only 4 cases had functional or hormonal syndrome (ZES with gastrin excessive), which is also similar to previous reports; 50-98% of D-NETs present no functional syndrome despite the positive immunoreactivity for gastrin, somatostatin, and/or serotonin in majority of D-NETs [5].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Corresponding results were also reported in the previous studies of D-NET [5,19,22]. In addition, only 4 cases had functional or hormonal syndrome (ZES with gastrin excessive), which is also similar to previous reports; 50-98% of D-NETs present no functional syndrome despite the positive immunoreactivity for gastrin, somatostatin, and/or serotonin in majority of D-NETs [5].…”
Section: Discussionsupporting
confidence: 78%
“…In addition to ENETS's recommendation of ER for NAD-NETs <10 mm in diameter, Burke et al [10] reported that there were no metastases identified in D-NETs <10 mm. Kim et al [22 ]also reported that 33 patients with D-NETs measuring ≤10 mm in diameter and confined to the submucosa demonstrated no recurrence following ER providing the absence of metastasis revealed by CT at the time of procedure. However, other studies did report metastasis in such tumors [11,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the minimal approach should be to resect tumors ≥10 mm. Resection should be performed by experienced endoscopists in gastric tumors using either EMR or endoscopic submucosal dissection (ESD); the latter has the benefit of an en bloc resection for complete histological appraisal and has been shown effective in a total of 96 patients [21,22,23,24]. Nonetheless, EMR and ESD do carry risks of bleeding and perforation.…”
Section: Treatmentmentioning
confidence: 99%
“…Malignant NET, such as type 3 gastric NETs which are considered to be aggressive and often with metastasis, can also be treated successfully by endoscopic treatment, including EMR [10] . Endoscopic resection appears to be a safe and effective treatment for duodenal carcinoid tumors measuring ≤ 10 mm in diameter and confined to the submucosal layer [11] .…”
Section: Discussionmentioning
confidence: 99%